Nutritional parameters of female goat kids fed diets containing detoxified castor bean cake - Araújo, Ricardo Alves de (2020)
The objective of this work was to evaluate the effect of replacing soybean meal (SM) by detoxified castor bean cake (DCC), containing different alkaline solutions, on the nutritional parameters of Saanen and Anglo-Nubian female goat (Capra aegagrus hircus) kids. The treatments consisted of three diets: one based on corn and SM; and two with DCC with Ca(OH)2 or NaOH. Intake and digestibility data were analyzed in two phases according to the growth curves of the goats, which showed: a linear accelerated growth (phase I, from 60 to 298 days of life) and a reduction in the intensity of body growth (phase II, from 299 to 345 days). During phase I, the goat kids fed DCC with NaOH showed a lower intake of dry matter (DM) and nutrients. During phase II, there was significant effect of diets on the intake of nutrients, with the exception of ether extract (EE), total digestible nutrients, and metabolizable energy (ME). A diet effect was observed on the digestibility of DM, crude protein, EE, and neutral detergent fiber, mainly for goat kids fed diets with DCC. Despite their lower intake, the diets formulated with DCC do not negatively affect the nutritional performance of female goats kids in both growth phases, since they result in a greater feed efficiency.